University in Translation : Internationalizing Higher Education. - Harris, Suzy (Continuum International Pub. Group, 2011)
What is the purpose of the university in a globalized and internationalized world? How do we talk about higher education? How is language used in higher education?. An instrumentalist and technical language - of 'impacts', 'outcomes', and 'targets' - has come to pervade political and educational discourse. Apparently more reliable than ordinary language, this technical discourse seems to promise a new objectivity in which everything that we need to know can be calculated and measured. Suzy Harris argues that the kind of language we use is critical to the kind of education we have, and that the.